2021
DOI: 10.3390/ijerph182111116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 Pandemic on Consumers’ Impulse Buying: The Moderating Role of Moderate Thinking

Abstract: Based on event systems theory, this study examined the impact of the COVID-19 pandemic on consumers’ impulse buying, as well as the underlying mechanisms and boundary conditions from the perspective of individual consumers. Results of three experiments (N = 437) show that, first, the COVID-19 pandemic enhanced consumers’ impulse buying behavior. Second, two key elements, loss of control and anxiety, mediated the relationship between the COVID-19 pandemic and impulse buying; and third, moderate thinking (also k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 87 publications
0
12
0
2
Order By: Relevance
“… Sheng et al (2019) revealed that Zhong Yong thinking is positively associated with green purchase intention among Chinese consumers based on three dimensions of consumer lifestyle (leadership, cost consciousness, and development consciousness). In addition, by indicating the moderating role of Zhong Yong thinking, Wang et al (2021) demonstrated that people make an effective shift from an emotion-based hot-processing system to a cognitive-based cold-processing system to acquire self-control in their behavior in the face of major occurrences such as the COVID-19 pandemic, which results in impulsive buying behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“… Sheng et al (2019) revealed that Zhong Yong thinking is positively associated with green purchase intention among Chinese consumers based on three dimensions of consumer lifestyle (leadership, cost consciousness, and development consciousness). In addition, by indicating the moderating role of Zhong Yong thinking, Wang et al (2021) demonstrated that people make an effective shift from an emotion-based hot-processing system to a cognitive-based cold-processing system to acquire self-control in their behavior in the face of major occurrences such as the COVID-19 pandemic, which results in impulsive buying behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous scholars have adopted Zhong Yong as a decision-making style and a type of characteristic, introducing Zhong Yong thinking as a moderator ( Tang et al, 2020 ; Wang et al, 2021 ). However, according to Rokeach (1968) , all interpretations of values are made up of three parts: a cognitive component that represents information, an affective component that can elicit feelings, and a behavioral component that is engaged when action is necessary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reason is that impulse buying leads to purchasing actions that are not based on considerations before entering the store (Mowen, 2008). Wang et al (2021) investigated that impulse buying occurs when consumers make a purchase by chance.…”
Section: Positive Emotions -Impulse Buyingmentioning
confidence: 99%
“…Impulse buying is defined as a spontaneous, unreflective, and unplanned purchase ( Lin et al, 2018 ). Impulse buying was a common occurrence across the world during the COVID-19 pandemic and led to irrational hoarding and waste of social resources, thereby resulting into disorder or even paralysis of the retail industry ( Gupta et al, 2021 ; Wang et al, 2021 ). According to Verplanken and Herabadi (2001) , impulse buying includes two core dimensions, namely cognitive and affective facets.…”
Section: Introductionmentioning
confidence: 99%